2017
DOI: 10.2196/jmir.6836
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Benefit of Telerehabitation After Orthopedic Surgery: A Systematic Review

Abstract: BackgroundIn addition to traditional physiotherapy, studies based on telerehabilitation programs have published the results of effectiveness, validity, noninferiority, and important advantages in some neurological, cognitive, and musculoskeletal disorders, providing an opportunity to define new social policies and interventions.ObjectivesThe aim of this systematic review is to investigate the effects of telerehabilitation after surgical procedures on orthopedic conditions as well as to describe how interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(140 citation statements)
references
References 61 publications
(95 reference statements)
6
116
0
12
Order By: Relevance
“…Enhanced patient and family education at the time of discharge via video, pictorials, or pharmacist visits is also effective in improving patient satisfaction and knowledge . There is emerging evidence that telehealth may enhance access to care and improve the patient experience . Nurse‐led postdischarge telephone calls have also been shown to improve patient satisfaction and follow‐up appointment attendance .…”
Section: Framing the Assessmentmentioning
confidence: 99%
“…Enhanced patient and family education at the time of discharge via video, pictorials, or pharmacist visits is also effective in improving patient satisfaction and knowledge . There is emerging evidence that telehealth may enhance access to care and improve the patient experience . Nurse‐led postdischarge telephone calls have also been shown to improve patient satisfaction and follow‐up appointment attendance .…”
Section: Framing the Assessmentmentioning
confidence: 99%
“…Other studies have looked at telehealth in follow‐up after joint arthroplasty and following fractures and found that overall home telehealth is at least as effective as usual care . A systematic review of telehealth for physiotherapy after orthopedic surgery found “strong evidence in favor of telehealth in patients following total knee and hip arthroplasty.”…”
Section: Specific Telehealth Applications For Neuromuscular or Musculmentioning
confidence: 99%
“…One such limitation is the lack of ability to blind both study subjects and providers to the intervention. In addition, it has been suggested that there may be bias in the telehealth groups due to more frequent contact with the therapists and team in comparison with usual care . Despite these challenges, future outcome studies should focus on access, quality of care, cost, prevention of readmission and morbidity/mortality, functional outcomes with standardized measures, and satisfaction of the patient and the provider.…”
Section: Limitationsmentioning
confidence: 99%
“…Orthopaedic surgeries are experiencing some of the greatest growth rates in developed nations across the world [4]. Decentralising orthopaedic outpatient consultations is of special interest, when a large number of patients live in remote areas, many of whom are not able to use public transport, or they need assistance by accompanying persons.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that teleorthopaedics in an outpatient setting is safe and without serious adverse events [13], that it has increased patient satisfaction [14,15] reduced travels and saved time for the patients [16,17] and reduced costs [18]. Teleorthopaedics can also improve the effectiveness of rehabilitation after orthopaedic surgery [4]. A study of paediatric orthopaedic patients found that even greater benefit can be obtained from telemedicine consultation for patients with a disability where the cost and inconvenience of patient transport is considerably increased [19].…”
Section: Introductionmentioning
confidence: 99%